Does a Firm’s Life Cycle Explain Its Propensity to Engage in Corporate Tax Avoidance? - Hasan, Mostafa; Al-Hadi, A.; Taylor, G.; Richardson, G. (Routledge Journals, 2016)
This study examines whether a firm’s life cycle explains its propensity to engage in corporate tax avoidance. Based on the Dickinson (2011) model of firm life cycle stages and a large dataset of US publicly listed firms over the 1987–2013 period, we find that tax avoidance is significantly positively associated with the introduction and decline stages and significantly negatively associated with the growth and mature stages using the shake-out stage as a benchmark. We observe a U-shaped pattern in tax avoidance outcomes across the various life cycle stages in line with the predictions of dynamic resource-based theory. Our findings are consistent using several robustness checks. Overall, our results show that a firm’s life cycle stage is a significant determinant of tax avoidance.